Use of Opuntia dillenii Seeds for Sorptive Removal of Acidic Textile Dyes from Water in Benign Way - Kanwal, Farah; Rehman, Rabia; Waheed Mushtaq, Muhammad; Batool, Aisha; Naseem, Shahzad (Asian Journal of Chemistry, 2013)
In this study, the use of Opuntia dillenii seeds (O.D.S) has been investigated as an adsorbent for removing two textile dyes i.e., drimarene blue K2RL and eosin B, from aqueous medium. Adsorption related factors, like adsorbent dose, contact time, pH of dye solution and temperature were optimized in batch mode by adopting one variable methodology for optimizing conditions. Then isothermal, thermodynamical and kinetic studies were carried out at optimized conditions of adsorption and it is found that maximum adsorption capacity of Opuntia dillenii seeds for removing drimarene blue K2RL and eosin B were 100 and 7.96 mg g-1, respectively, following pseudo-second order kinetic model. Ethanol and NaOH were found suitable for regenerating used Opuntia dillenii seeds as compared to HCl or water. So, Opuntia dillenii seeds can be effectively employed for waste water treatment in economical way, using indigenous sources.